Extracellular Vesicle-Derived microRNA-410 From Mesenchymal Stem Cells Protects Against Neonatal Hypoxia-Ischemia Brain Damage Through an HDAC1-Dependent EGR2/Bcl2 Axis - Han, Jun; Yang, Si; Hao, Xiaosheng; Zhang, Bo; Zhang, Hongbo; Xin, Cuijuan; Hao, Yunpeng (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia-ischemia brain damage (HIBD) is a neurological disorder occring in neonates, which is exacerbated by neuronal apoptosis. Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been proposed as a promising strategy for treating or preventing ischemia-related diseases. However, their mechanisms in HIBD remain unclear. Thus, we aimed to address the role of EV-derived microRNA (miR)-410 in HIBD. Neonatal HIBD mouse model was constructed using HI insult, from which neurons were isolated, followed by exposure to oxygen glucose deprivation (OGD). EVs were isolated from human umbilical cord (hUC)-derived MSCs. In silico analyses, dual-luciferase reporter gene and chromatin immunoprecipitation assays were adopted to determine relationships among miR-410, histone deacetylase 1 (HDAC1), early growth response protein 2 (EGR2) and B cell lymphoma/leukemia2 (Bcl2). The functional roles of EV-derived miR-410 were determined using loss- and gain-of functions experiments, and by evaluating neuronal viability, cell-cycle distribution and neuronal apoptosis in vitro as well as modified neurological severity score (mNSS), edema formation, and cerebral infarction volume in vivo. hUC-MSCs-derived EVs protected against HIBD in vivo and inhibited the OGD-induced neuronal apoptosis in vitro. miR-410 was successfully delivered to neurons by hUC-MSCs-EVs and negatively targeted HDAC1, which inversely mediated the expression of EGR2/Bcl2. Upregulation of EV-derived miR-410 promoted the viability but inhibited apoptosis of neurons, which was reversed by HDAC1 overexpression. EV-derived miR-410 elevation reduced mNSS, edema formation, and cerebral infarction volume by increasing EGR2/Bcl2 expression through downregulating HDAC1 expression in vivo. In summary, EV-derived miR-410 impeded neuronal apoptosis by elevating the expression of EGR2/Bcl2 via HDAC1 downregulation, thereby providing a potential strategy for treating or preventing HIBD.